Jual Beli secara Online dalam tinjauan Hukum Islam - WAHIBATUL MAGHFUROH (JAS : Jurnal Ahwal Syakhshiyyah, 2020)
Online transactions are order transactions in a global era business model that is not face-to-face, with only conducting data transfers via cyberspace (data intercange) via the internet between the two parties, namely sellers and buyers, this information technology development enables remote transactions, where anyone can interact even without face to face (face to face). In online business the most important thing is the availability of information and the benefits. Or what is now better known as e-business or e-commerce, the type of research used in this research is library research, buying and selling online including aspects of muamalah which are basically permissible. Unless there is an argument forbidding it. In addition, the terms and conditions of online purchase agreement also do not conflict with the terms and conditions of the Islamic legal system of engagement.